DANP-based method for determining the adoption of hospital information system. (28th November 2019) - Shahzad, Khuram; Jianqiu, Zeng; Zubedi, Asma; Xin, Wen; Wang, Lei; Hashim, Muhammad
The primary purpose of this study is to identify the essential factors that are significantly driving or hindering the decision to adopt a hospital information system (HIS). This study proposes the initial theoretical model that integrates Technology Organisation Environment (TOE) framework, Human Organisation Technology (HOT) fit model and institutional theory. The initial model consists of four main dimensions and 13 variables, which are the most frequently used in prior literature and essential for the investigation of HIS adoption. The data were collected from healthcare experts who have full knowledge of HIS. Accordingly, the recently developed DANP (Decision Making Trial and Evaluation Laboratory (DEMATEL) based Analytic Network Processes (ANP)) method is employed for assessing interdependency and give weights to dimensions and criteria. As per the expert's knowledge and experience, the results indicate that perceive technical competence, compatibility, top management support, and vendor support are found to be the most essential variables for the successful adoption of HIS.